Pengaruh Kombinasi Probiotik, Ubi Jalar Ungu, dan Zinc terhadap Tebal Epitel Usus Mencit Jantan BALB/c Kolitis Ulseratif terinduksi Asam Asetat: Effect of Combination of Probiotics, Ipomoea Batatas, and Zinc on Thickness of Instestinal Epithelium in Mice Model of Acetic Acid-Induced Colitis - Tsuraya, Ghefira; Yuniarifa, Conita; Hussaana, Atina; Riza, Mohamad; Masfiyah, Masfiyah (Universitas Airlangga, 2025)
Background: The use of probiotics to treat colitis is unsatisfactory, leading to a need for the combination with purple sweet potatoes (Ipomoea Batatas) and zinc. Objectives: This study aims to determine the effect of the combination of probiotics, purple sweet potatoes, and zinc on epithelial thickness.Methods: This was a post-test-only randomized controlled group experimental study using 30 mice divided into six groups, including KN, K-, K+, P1, P2, and P3. All groups except KN were induced with 4% acetic acid on day 1, then each received treatment for five days. KN, K+, P1, and P2 groups were given distilled water, sulfasalazine 1.3 mg/20 g BW, probiotics 0.078 mg/20 gBW + purple sweet potatoes 0.00169 g/20 gBW, and probiotics 0.078 mg/20 gBW + zinc 0.052 mg/20 gBW, respectively. Meanwhile, P3 received a combination of probiotics 0.078 mg/20 gBW + purple sweet potatoes 0.00169 g/20 gBW + zinc 0.0052 mg/20 gBW. Histological preparations were stained with Hematoxylin-Eosin and examined under 400× magnification across 10 fields of view. Results: The average epithelial thicknesses were KN (75.48±5.09), K− (28.02±5.60), K+ (69.1±13.82), P1 (47.05±9.41), P2 (48.6±9.73), and P3 (71.57±14.31). One-way analysis of variance (ANOVA) showed a significant difference among the groups with a p-value <0.001. Post Hoc LSD test identified significant differences (p-value<0.05) among all group pairs except between K+ and P3 (p-value=0.134) as well as P1 and P2 (p-value=0.349), but P3 had the highest average thickness value (71.57±14.31).Conclusions: The combination of probiotics, purple sweet potatoes, and zinc had an effect on intestinal epithelial thickness in male BALB/c mice with ulcerative colitis.